Emotional prosperity and the Stiglitz Commission - Andrew J. Oswald (Institute for the Study of Labor (IZA), 2010)
This paper argues - in line with the proposals of the recent Stiglitz Commission on the Measurement of Economic Performance and Social Progress - that we should now be measuring a nation's emotional prosperity rather than its economic prosperity (that is, we ought to focus on the level of mental well-being not the number of pounds in people's bank accounts). The paper reviews recent ideas in this field. It also describes seven recent studies that, worryingly, suggest that emotional prosperity may be declining through time. For labour-market specialists, a key question for future research is how much this downward trend can be traced back to increased pressures in working life. That question currently remains open.
Keywords: I1; I3; 330; well-being; biomarkers; GHQ; happiness; Easterlin paradox